Pengetahuan dan Motivasi Dengan Sikap Perawat dalam Pemenuhan Kebutuhan Spiritual Pasien di Ruang Rawat Inap RSUD Dr. H. Chasan Boesoirie Ternate - Albaar, Fuad (Jurnal Kesehatan Poltekkes Ternate, 2014)
Abstract : One aspect of professional services in nursing is a matter of spiritual fulfillment, but in fact the spiritual needs of patients less attention by the nurses. This study aims to determine the related to the attitude of the nurse in meeting the spiritual needs of patients. Comparative research design using a cross sectional analytic study, samples were taken using a nonprobability sampling with purposive sampling, sample number 95 nurses working in the inpatient Medical-Surgical Hospital Dr. H. Chasan Boesoirie Ternate. Data collection using questionnaires to measure the level of knowledge, motivation and attitude of nurses in meeting the spiritual needs of patients. Data analysis using Chi-Square test to see the correlation between education, knowledge and motivation to nurse attitudes, whereas multivariate analysis is used to see the most dominant factors related to nurse attitudes. In this study, the results obtained by respondents who had a positive attitude as much as 36.8%, a negative attitude as much as 63.2%. Chi-Square test results with the attitude of educational factors (p = 0.007), knowledge (p = 0.003), motivation (p = 0.004). Multivariate analysis showed the most dominant factor is related to the attitude of education (Exp (B) = 5.704). It is concluded that there is a significant relationship between education, knowledge and motivation with the attitude of nurses in meeting the spiritual needs of patients in the inpatient Medical-Surgical Hospital Dr. H. Chasan Boesoirie Ternate. The higher the education nurses tend to be more positive attitude, while the lack of knowledge and low motivation of the nurses tend to be more negative the attitude in meeting the spiritual needs of patients. The dominant factor is related to the attitude of education. It is hoped that further enhance human resources related to quality nursing services in general and in particular in meeting the spiritual needs of patients through the application of holistic nursing care.